From Biological Control to Invasion: the Ladybird Harmonia axyridis as a Model Species - Roy, Helen E. (Springer, 2017)
Harmonia axyridis has been described as the "most invasive ladybird on Earth". It has a long history of use as a classical biological control agent in the USA and more recently in Europe. This beetle has been effective at controlling pest insects in a variety of crop systems but it poses unacceptable risks by impacting on non-target species as both an intraguild predator and competitor. Written by renowned scientists, this book is a synthesis of recent research on H. axyridis and provides informative insights into current perspectives and future directions. Biological control is an essential component of sustainable agriculture but the distinction between a successful biological control agent and an invasive species can be narrow. We hope that lessons can be learnt from H. axyridis.